Guiding Effect of Serum Procalcitonin (PCT) on the Antibiotic Application to Patients with Sepsis - Yu LIU; Weize YANG; Jie WEI (Tehran University of Medical Sciences, 2017)
Background: This study aimed to investigate the guiding effect of serum procalcitonin (PCT) on the antibiotic application to patients with sepsis. Methods: Ninety-eight patients with sepsis treated in Renmin Hospital of Wuhan University, China from 2015-2017 were enrolled. They were divided into two equal groups of control group and the observation group. Patients in the observation group received the antibiotic therapy guided by PCT while patients in the control group received the regular antibiotic therapy. The conventional indexes, prognosis and clinical effects of the two groups were compared. Results: There were no statistical significance in the differences of the Acute Physiology and Chronic Health Evaluation II (APACHE-II) scores C-reactive protein (CRP) and white blood cell count (WBC) levels between the two groups. The duration of the antibiotic application to patients in the observation group was (7.74±0.61) d which was (10.22±0.78) d shorter than that to patients in the control group. The difference was statistically significant (P<0.05). The Intensive Care Unit (ICU) stay time and the hospital stays of patients in the observation group were shorter than those of patients in the control group. The difference had statistical significance (P<0.05). The difference in 30-day-recurrence rate and 30 day-mortality of the patients in the two groups had no statistical significance. There was statistically significant difference in the comparison of the clinical effects between the two groups. Conclusion: Guiding effects of the serum PCT on the application of antibiotics to patients with sepsis shorten the usage time of the antibiotics, ICU stay time and hospital stays.